2007
DOI: 10.1182/blood-2007-02-072843
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of cytokine and suicide genes to enhance the activity and safety of tumor-specific cytotoxic T lymphocytes

Abstract: The antitumor effect of adoptively transferred tumor-specific cytotoxic T lymphocytes (CTLs) is impaired by the limited capacity of these cells to expand within the tumor microenvironment. Administration of interleukin 2 (IL-2) has been used to overcome this limitation, but the systemic toxicity and the expansion of unwanted cells, including regulatory T cells, limit the clinical value of this strategy. To discover whether transgenic expression of lymphokines by the CTLs themselves might overcome these limitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
147
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(155 citation statements)
references
References 41 publications
8
147
0
Order By: Relevance
“…Encouraged by the successful use of 2A peptides in g-retroviral vectors to express multiple genes in one construct, 24,25,27 we attempted to develop lentiviral vectors expressing antitumor antigen-specific TCRs using different 2A peptides. In Figure 1a, the amino acids from different 2A peptides are illustrated and the conservative domains highlighted.…”
Section: A Peptides Along With Furin and Spacer Facilitate Transgenementioning
confidence: 99%
See 2 more Smart Citations
“…Encouraged by the successful use of 2A peptides in g-retroviral vectors to express multiple genes in one construct, 24,25,27 we attempted to develop lentiviral vectors expressing antitumor antigen-specific TCRs using different 2A peptides. In Figure 1a, the amino acids from different 2A peptides are illustrated and the conservative domains highlighted.…”
Section: A Peptides Along With Furin and Spacer Facilitate Transgenementioning
confidence: 99%
“…An alternative to these approaches is the use of ribosomal skipping via 2A peptides. 23,24 Several viruses use 2A peptides to mediate protein cleavage, including foot-and-mouth disease virus (F2A), equine Rhinitis A virus, porcine teschovirus-1 (P2A) and Thosea asigna virus (T2A). The 2A peptide consensus motif (DVEXNPGP) is extremely rare and is associated with cleavage-like activity between 2A and 2B genes through a ribosomal skip mechanism; the 2A peptide impairs normal peptide bond formation between 2A and 2B without affecting the translation of 2B.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This goal might be either achieved by expressing homeostatic cytokines, 76 or cognate receptors 77 into T lymphocytes, or by gene transfer and expansion of selected T-cell sub-populations with retroviral and lentiviral vectors. 78 We showed that a potent activation with cell-sized beads conjugated with antibodies directed to CD3 and CD28 recruits in cell cycle, thus facilitating retroviral transduction of naive and central memory (T CM ) lymphocytes.…”
Section: Graft-versus-host Disease S Mastaglio Et Almentioning
confidence: 99%
“…As an important T cell growth factor, IL-15 has been demonstrated to prolong the persistence of adoptively transferred cytotoxic T cells (CTLs) in vivo (Quintarelli et al, 2007). The major effects of IL-15 on T cells include (1) enhanced cytotoxic ability and proliferation of CTLs in vivo (Klebanoff et al, 2004), (2) activation of the telomerase and elongation of telomeres (Li et al, 2005), (3) ability to rescue tumor-tolerant T cells for use in adoptive immunotherapy (Teague et al, 2006), and (4) inhibition of activation-induced cell death of T cells (Marks-Konczalik et al, 2000).…”
Section: Introductionmentioning
confidence: 99%